Pengembangan Sistem Informasi Berbasis Web Untuk Pengolahan Data Kerjasama, Kegiatan Mahasiswa, Dan Prestasi Mahasiswa Di Fakultas Teknologi dan Rekayasa Cerdas Universitas Kristen Maranatha - Nicole Jade Tirtanimala; Wenny Franciska Senjaya (Journal of Smart Technology and Engineering, 2026)
The management of cooperation data, student activities, and student achievements at the Faculty of Technology and Intelligent Engineering (FTRC) still faces several issues in terms of efficiency, accuracy, and data availability. To address these problems, a web- based integrated information system was developed to facilitate the recording, management, and reporting of data within the faculty. This system includes core modules such as user account management, student organization activities (HIMA/SEMA), DPBA activities, student achievements, institutional cooperation (MoU/PKS/IA), and system activity logs. The system was developed using the waterfall method and tested through blackbox testing to ensure each function operates according to the requirements. Test results showed that all modules functioned correctly as designed. The implementation of this system improves the efficiency of data processing and supports more accurate and faster administrative processes and decision-making at the faculty level.